2015
DOI: 10.1111/pme.12886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of How Depression and Anxiety Mediate the Relationship between Pain Catastrophizing and Prescription Opioid Misuse in a Chronic Pain Population

Abstract: Due to the partially independent relationship of anxiety and catastrophizing, it is recommended that treatments for chronic pain patients employ techniques addressing both behaviors. The relationship between depression and catastrophizing requires more research since it was observed that their effects were confounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 45 publications
(73 reference statements)
8
53
2
1
Order By: Relevance
“…Prior studies have shown that chronic pain is an independent risk factor for increased postoperative opioid use [7, 10, 11], while other studies have shown that anxiety is also linked to an increase in use of opioids [12, 13]. Although our results did not show a statistically significant difference in those with and without anxiety, depression or chronic pain, participants with these health conditions seemed to be less likely to think they were overprescribed opioids.…”
Section: Discussioncontrasting
confidence: 83%
“…Prior studies have shown that chronic pain is an independent risk factor for increased postoperative opioid use [7, 10, 11], while other studies have shown that anxiety is also linked to an increase in use of opioids [12, 13]. Although our results did not show a statistically significant difference in those with and without anxiety, depression or chronic pain, participants with these health conditions seemed to be less likely to think they were overprescribed opioids.…”
Section: Discussioncontrasting
confidence: 83%
“…21 Given the positive associations found between catastrophizing and the aforementioned opioid responses and behaviors, it would follow that a similar association might exist for catastrophizing and receipt of opioid prescription in a larger civilian chronic pain population. However, to our knowledge, this latter relationship is unexplored.…”
Section: Introductionmentioning
confidence: 95%
“…It has been found that in individuals with chronic non-cancer pain, the presence of co-morbid mental health diagnoses, particularly mood disorders, predicts the likelihood of opioid prescription, 21 the degree of opioid use, 11 and the likelihood of aberrant opioid use (e.g., opioid abuse or dependence). 22 Consequently, we sought to characterize the relationship between pain catastrophizing and opioid prescription independent of the influences of these and other factors, including age, 11 sex, 23 and pain intensity, 16,24 known to be relevant to opioid use and pain catastrophizing, such as symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…All of these behavioral comorbidities are strongly associated with chronic opioid use, misuse, and dependence (Turk et al 2008 ; Becker et al 2008 ; Goldner et al 2014 ; Gross et al 2016 ; Arteta et al 2016 ; McAnally 2017 ) and in fact have been shown repeatedly to be the most robust predictors (Martins et al 2012 ; Katz et al 2013 ; Blanco et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%